2019
DOI: 10.1523/jneurosci.0076-19.2019
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Sensory Encoding to Measured Bias

Abstract: Signal detection theory (SDT) is a widely used theoretical framework that describes how variable sensory signals are integrated with a decision criterion to support perceptual decision-making. SDT provides two key measurements: sensitivity (d) and bias (c), which reflect the separability of decision variable distributions (signal and noise) and the position of the decision criterion relative to optimal, respectively. Although changes in the subject's decision criterion can be reflected in changes in bias, deci… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 55 publications
5
17
0
Order By: Relevance
“…While Ai203 is particularly advantageous for 2p optogenetics, the potent st-ChroME expression will also assist in applications involving conventional 1p activation. As one example, we demonstrated that 1p activation of V1 in Vglut1-Cre;Ai203 mice altered performance in a detection task, matching previous findings using channelrhodopsin in excitatory neurons (Cone et al, 2020;Jin & Glickfeld, 2019). In addition, soma-targeting is important for less conventional 1p approaches where spatial resolution with 1p illumination is needed (Wu et al, 2013;Xue et al, 2020).…”
Section: Discussionsupporting
confidence: 82%
“…While Ai203 is particularly advantageous for 2p optogenetics, the potent st-ChroME expression will also assist in applications involving conventional 1p activation. As one example, we demonstrated that 1p activation of V1 in Vglut1-Cre;Ai203 mice altered performance in a detection task, matching previous findings using channelrhodopsin in excitatory neurons (Cone et al, 2020;Jin & Glickfeld, 2019). In addition, soma-targeting is important for less conventional 1p approaches where spatial resolution with 1p illumination is needed (Wu et al, 2013;Xue et al, 2020).…”
Section: Discussionsupporting
confidence: 82%
“…Irrespective of whether side choice behavior is innate or learned, the fact that we could use it to identify subjects clearly indicates that this behavior should have a stable internal representation, one which could derive from functional asymmetries in neuronal circuitry. Internal factors and asymmetries in sensory encoding and inhibitory control have been associated with choice biases ( Langen et al, 2011 ; Novak et al, 2016 ; Jin and Glickfeld, 2019 ; Linares et al, 2019 ). Most importantly, stereotypies in mice could share some mechanisms with stereotypies in human mental disorders ( Langen et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, this is most likely because of an adaptation-dependent reduction in firing rates in response to both targets and distractors (i.e., signal and noise), which will decrease the optimal criterion (and increase bias because bias is measured relative to optimal). Thus, changes in sensory processing in V1, in the absence of cognitive mechanisms whereby the mouse increases its criterion, are sufficient to explain this change in bias (Witt et al, 2015;Jin and Glickfeld, 2018). The lack of effect of ISI on lapse rate also argues against a cognitive mechanism for the effects of ISI on behavior.…”
Section: °4mentioning
confidence: 99%